STUDY ON METABOLIC PROFILE OF REPEAT BREEDER, POST PARTUM ANESTROUS AND NORMAL CYCLIC SAHIWAL COWS
This study was conducted with the aim to investigate comparative metabolic profile of repeat breeder, post partum anestrous and normal cyclic Sahiwal cows. A total of 18 Sahiwal Cows having body weight 300 to 400 kg, second to fifth lactation and age between four to nine years, were divided into three groups (Normal Cyclic, Repeat breeder and Anestrous); each group comprised of 06 animals. Blood samples were collected aseptically and serum was separated by centrifugation at 3000 rpm for 10 minutes to analyze the glucose (mg/ di), total protein (g/dl